Adaptive output-feedback control for switched stochastic uncertain nonlinear systems with time-varying delay. (April 2018) - Song, Zhibao; Zhai, Junyong
Abstract: This paper addresses the problem of adaptive output-feedback control for a class of switched stochastic time-delay nonlinear systems with uncertain output function, where both the control coefficients and time-varying delay are unknown. The drift and diffusion terms are subject to unknown homogeneous growth condition. By virtue of adding a power integrator technique, an adaptive output-feedback controller is designed to render that the closed-loop system is bounded in probability, and the state of switched stochastic nonlinear system can be globally regulated to the origin almost surely. A numerical example is provided to demonstrate the validity of the proposed control method. Highlights: Compared with y = z 1 in [25, 28 ], z 1 cannot be precisely estimated by y owing to uncertain function y = h ( z 1 ) . Particularly, y = β z 1 in Ref. [32 ] is a special case of system(1) with b 1 = b 2 = ⋯ = b n = 1 . Distinct from Ref. [33 ], a new adaptive output-feedback controller is designed under a weak situation that the nonlinearities satisfy unknown homogeneous growth condition. Our results extend the existing global stabilization results for non-switched stochastic systems without time delay to switched stochastic time-delay nonlinear systems.